Whole-Cell Postbiotics: an Innovative Approach for Extending the Shelf Life and Controlling Major Foodborne Pathogens in Chicken Breast Fillets - Incili, Gokhan Kursad; Akgol, Muezeyyen; Karatepe, Pinar; Tekin, Ali; Kanmaz, Hilal; Kaya, Busra; Hayaloglu, Ali Adnan (Springer, 2023)
The current research was designed to compare the physicochemical and antimicrobial properties of cell-free supernatant (CFS) and whole-cell postbiotic (WCP) and reveal the efficacy of WCP in combination with chitosan and thymol for extending the shelf life and inhibiting emerging foodborne pathogens in chicken breast fillets during storage at 4 degrees C. For this purpose, pH, organic acids, titratable acidity, antioxidant capacity assays (FRAP, ABTS, and DPPH), free amino acids (FAA), free fatty acids (FFA), total phenolic content, individual phenolics, color properties, and volatiles of CFS and WCP were compared. The levels of some organic acids, FAA, titratable acidity, and total phenolic content (TPC) of WCP were higher than CFS (P < 0.05). Almost similar inhibition zones (7.82 to 10.43 mm) were recorded between the CFS and WCP against some pathogenic bacteria including S. Typhimurium, E. coli O157:H7, and L. monocytogenes. In chicken breast fillets, the total viable count of the control group reached the upper limit (7.0 log(10)) on the 6th day, while WCP (50%) + thymol (0.5%) + chitosan (0.5%) treatment provided a shelf life extension of 9 days (P < 0.05). Additionally, this treatment provided 2.35, 2.35, and 1.96 log(10) CFU/g reductions in S. Typhimurium, E. coli O157:H7, and L. monocytogenes counts on the initial day, respectively (P < 0.05). The result of this study revealed that WCPs can be easily prepared without any changes in antibacterial efficacy and used in food matrices to control major foodborne pathogens and extended the shelf life by retarding microbial and chemical deteriorations.
Keywords: Whole-cell postbiotic; Cell-free supernatant; Physicochemical composition; Foodborne pathogens; Chicken breast fillets